Making the numbers: CPFR and S&OP Continuum - Sagar, Nikhil (Henry Stewart Talks, 2010)
Right place, right time, Possible disconnects in a non collaborative space, Multiple forecasts, Cost of disconnects, Collaboration, Continuum, Forecasting, S&OP agenda and forecasting, S&OP demand shaping, Qualitative enrichments, CPFR, Closing the loop, Weekly business rhythm, Conclusions